The sex- and duration-dependent effects of intermittent fasting on lifespan and reproduction of spider mite Tetranychus urticae - Guang-Yun Li; Zhi-Qiang Zhang (Frontiers in Zoology, 2019)
Abstract Background Intermittent fasting (IF) is receiving increasing attention as an alternative to continuous restriction of calories because of its benefits in aging-related disease prevention and lifespan extension. However, whether both sexes with sexual dimorphism have similar response to IF have rarely been assayed. In this study, we determined how different durations of IF influence lifespan and whether males and females differed in their responses to IF. We also tested whether there is a trade-off between lifespan and lifetime reproduction in females under IF. Method We used spider mite Tetranychus urticae, with female-biased sexual size dimorphism (SSD), as our model species to investigate the survival and lifespan difference of both sexes at different durations of IF regimes, and explore the association between longevity and fecundity in females within and across treatments. Results The lifespan of females increased before intermediate level of IF and then decreased afterwards, but males showed a decreasing trend in lifespan when subjected to IF. Within each treatment, female longevity was positively associated with their fecundity. However, the females fed ad libitum had a higher lifetime fecundity with a shorter lifespan, whereas mites fed 50% IF outlived ad libitum fed ones with lower fecundity because of the later onset of reproduction and lower daily fecundity, showing clear survival and reproduction trade-off when variation of resource availability enhanced across treatments. Conclusion We showed sex-specific response to IF in lifespan, indicating that sexes with SSD have different optimal level of IF. These findings showed trade-off between survival and reproduction between treatments but not within treatments, suggesting that variation in resource availability is the necessary precondition for life history trade-off, and IF extends lifespan of females at the cost of reproductive success.